Molecular Docking Analysis of Liliaceae FamilyPhytochemicals to Estrogen Receptor Î± on Breast Cancer Compared to Genistein - Permana, Bryan Pandu; Pesik, Riza Novierta; Hakim, Fikar Arsyad (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Breast cancer is the second highest cancer incidence in the world with 1.7 million women were diagnosed in 2012. Interaction between estrogen and estrogen receptor Î± (ERÎ±) have an important role in cancer progressivity and resistancy to chemotherapy. Genistein is one of the phytoestrogen that has selective estrogen receptor modulator (SERM) activity so it can inhibit the activity of estrogen receptor Î± (ERÎ±) on the breast cancer. Other phytochemicals are expected to have more affinity to ERÎ± than genistein. Anticancer activity of Liliaceae family phytochemicals have been found but its inhibition to ERÎ± is unknown.Â This research analyzes the interaction between Liliaceae phytochemicals to ERÎ± by molecular docking technique. Method: This research is bioinformatics observational research that observed the interaction between Liliaceae phytochemicals to ERÎ±. The molecular docking analysis was performed using PLANTS 1.1, preparation program MarvinSkecth 5.2 and YASARA 10.1. Visualization of the molecular docking was performed using PyMOL 1.3. Results: Six substances have lower docking score than genistein (-79.21). Those are spiraeoside (-84.80), stigmasterol (-84.28), cyanin (-83.79), beta-sitosterol (-82.81), progesterone (-82.68) and idaein (-82.22). Spiraeoside, cyanin, and idaein have one or more hydrogen bond to ERÎ± in visualization. The six substances bind ERÎ± on four same amino acids that bindgenistein, those are Trp383, Leu525, Met528, and Cys530. Conclusio: Molecular docking analysis of Liliaceae phytochemicals found six substances that have higher affinity to ERÎ± than genistein with three substances have hydrogen bond and similar structure to the genistein. Keyword: Breast Cancer, Estrogen Receptor Î±, Genistein, Liliaceae Family Phytochemical, Molecular Docking.